Previous History of Migraine Is Associated With Fatigue, but Not Headache, as Long-Term Post-COVID Symptom After Severe Acute Respiratory SARS-CoV-2 Infection: A Case-Control Study - Fernández-de-las-Peñas, César; Gómez-Mayordomo, Víctor; García-Azorín, David; Palacios-Ceña, Domingo; Florencio, Lidiane L.; Guerrero, Angel L.; Hernández-Barrera, Valentín; Cuadrado, María L. (Frontiers in Human Neuroscience, 2021)
Objective: To investigate the association of pre-existing migraine in patients hospitalised and who recovered from SARS-CoV-2 infection with the presence of post-COVID symptoms. Background: No study has investigated the role of migraine as a risk factor for development of post-COVID symptoms. Methods: A case-control study including individuals hospitalised during the first wave of the pandemic (from February 20 to May 31, 2020) was conducted. Patients with confirmed previous diagnosis of migraine were considered cases. Two age- and sex-matched individuals without a history of headache per case were also recruited as controls. Hospitalisation/clinical data were collected from hospital medical records. Patients were scheduled for a telephone interview. A list of post-COVID symptoms was systematically evaluated, but participants were invited to freely report any symptom. The Hospital Anxiety and Depression Scale and the Pittsburgh Sleep Quality Index were used to assess anxiety/depressive symptoms and sleep quality. Multivariable conditional logistic regression models were constructed. Results: Overall, 57 patients with confirmed diagnosis of migraine and 144 non-migraine controls who had recovered from COVID-19 were assessed at 7.3 months (SD 0.6) after hospital discharge. The number of post-COVID symptoms in the migraine group was significantly greater (OR 1.70 95%CI 1.29-2.25, P<0.001) than in the non-migraine group. Fatigue was significantly more prevalent (OR 2.89 95%CI 1.32-6.32, P=0.008) in the migraine group. However, no between-groups difference in the prevalence of headache as a post-COVID symptom was detected. Conclusions: Patients with a history of migraine who recovered from COVID-19 exhibited more long-term fatigue as post-COVID sequelae than those without migraine. Some of the pathophysiological changes associated with migraine could predispose to the occurrence of post-COVID symptoms.